Investigar, leer y escribir en la universidad: recorridos de estudiantes ingresantes de Humanidades - Padilla, Constanza; Douglas, Silvina; Lopez, Esther (Enunciación, 2014)
University studies require students to enter in a disciplinary culture where the production of knowledge and the ways of communicating them imply a learning process that teachers should guide. In order to contribute to the discussion about didactical alternatives of academic reading and writing in higher education, we link them with the development of a research carried out by students, where they had to coordinate theoretical sources and articulate them with empirical data. To do so, through narratives of writing tutors that allow us to appreciate the interplay between processes of scaffolding and autonomy, we present some qualitative results from action-research cycles developped in an asignature of Hummanities from a public University in Argentina. In this Hummanities asignature, students approximate themselves to the ways of production, circulation and legitimation of disciplinary knowledge by means of writing and defending a conference paper.